2012
DOI: 10.1007/s10815-012-9719-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of male age on the outcome of in vitro fertilization: oocyte donation as a model

Abstract: Purpose To assess the influence of male age on the outcome of oocyte donation cycles. Materials and methods A total 103 oocyte donation cycles of 70 couples (male aged 26 to 57) were examined, all of which were performed with conventional in vitro fertilization using fresh ejaculation sperm. Main outcome measures were fertilization rate, clinical pregnancy, live birth rates and pregnancy loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
2
15
1
Order By: Relevance
“…For the comparisons of interrater reliability, the kappa coefficient was 0.86 during the abstract review (95% confidence interval [CI] 0.75-0.97) and 0.92 in the full-text stage (95% CI, 0.76-1.0). Finally, of 425 initial references, twelve manuscripts encompassing 12,538 oocyte donation cases were included in the review (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Table 1 summarizes the characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…For the comparisons of interrater reliability, the kappa coefficient was 0.86 during the abstract review (95% confidence interval [CI] 0.75-0.97) and 0.92 in the full-text stage (95% CI, 0.76-1.0). Finally, of 425 initial references, twelve manuscripts encompassing 12,538 oocyte donation cases were included in the review (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Table 1 summarizes the characteristics of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…De la Rochebrochard reported that paternal age had a detrimental effect on pregnancy rates in conventional in vitro fertilization (IVF) cycles in cases of paternal and maternal ages >40 y and >35 y, respectively [ 4 ]. However, discrepancies exist when considering oocyte-donation cycles; while some studies indicated a negative influence on embryo quality, implantation rate and live birth rate [ 5 8 ], others suggested no effects on the rates of pregnancy, miscarriage and live births [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are in line with the results of studies. 23,[32][33][34][35] A study by Wu et al, showed that there was no difference between the amount of pregnancy and implantation among different male age groups 35 while De la Rochbrochardet al, reported that the age of parents (fathers over 40 years old and mothers over the age of 35) significantly affects fertility in IVF. 29 In this study, there was no significant relationship between sperm motility and IVF.…”
Section: Discussionmentioning
confidence: 99%
“…23 Some studies over the effect of age have shown significant reductions in fertility, live birth, embryo quality and implantation, 24-,30 but others have suggested that age does not affect fertility, abortion and live birth. [31][32][33][34][35] According to Atkinson et al, concentration and sperm motility do not affect the fertility and delivery efficacy in IVF and IUI 36 , but another study suggests that very low sperm motility reduces fertility rates in IVF and ICSI. 37 A number of studies have also shown that leukocytospermia has a negative effect on the efficiency of IVF and ICSI, [38][39][40][41][42][43][44] but some studies have also shown that leukocytospermia has no effect on the incidence of pregnancy and fertility after IVF and ICSI.…”
Section: Introductionmentioning
confidence: 99%